2017
DOI: 10.3390/economies5030027
|View full text |Cite
|
Sign up to set email alerts
|

Regional Economic Convergence in Turkey: Does the Government Really Matter for?

Abstract: Solow (1956) has made an essential contribution to the Neo-classical growth approach through the economic convergence hypothesis. It assumes that poorer countries' or regions' per capita incomes tend to grow at faster rates than the richer ones. Convergence could occur either among a group of economies with the same steady states or within regions in which their fundamental dynamics differ, and thus they exhibit multiple steady states. This study aims to investigate convergence with respect to GDP per capita a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
9
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 32 publications
4
9
0
1
Order By: Relevance
“…These amounts were realized as realization of 2,044.5 billion TL in 2014 and loss of social welfare of 221 billion TL in GDP felt as 1,823.5 billion TL (See Table 2). Karaca (2018) for the period between 2000-2010, Gündem (2017) for the period between 2004-2011, Gömleksiz et al (2017 for the period between 2004-2014 found a decrease in income inequality between regions. In contrast, Karahasan (2017) argued that regional inequalities for the period 2004-2014 have become permanent.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These amounts were realized as realization of 2,044.5 billion TL in 2014 and loss of social welfare of 221 billion TL in GDP felt as 1,823.5 billion TL (See Table 2). Karaca (2018) for the period between 2000-2010, Gündem (2017) for the period between 2004-2011, Gömleksiz et al (2017 for the period between 2004-2014 found a decrease in income inequality between regions. In contrast, Karahasan (2017) argued that regional inequalities for the period 2004-2014 have become permanent.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, since 2011 there have been at least eight more studies analyzing regional inequality based on the 2004 data set and later. These are: Abdioğlu and Uysal, 2013;Karahasan, 2015;Uyaner and Volkan, 2016;Gündem, 2017;Gömleksiz et al, 2017;Karahasan, 2017;Tuğrul, 2017;Karaca, 2018.…”
Section: Introductionmentioning
confidence: 99%
“…One of the main reasons for this study is to reveal the impact of investment incentives on the high level of regional differences in Turkey. The relationship between investment incentives, public expenditures, regional differences, and economic growth and development in Turkey has always attracted attention (Tansel and Güngör, 1999;Sağbaş, 2002;Yıldırım et al, 2009;Zeren and Yılancı, 2011;Gömleksiz et al, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…There are also regional studies examining the effects of investment incentives for Turkey (Karaalp, 2014;Selim et al, 2014;Demirtaş and Aksel, 2018;Baykul et al, 2019). Gerni et al (2015), Sevinç et al (2016) and Gömleksiz et al (2017) determined that the investment incentives had positive impacts on economic growth in 26 development regions of Turkey for different years. Sağbaş et al 's (2016) study obtained significant findings among the regional studies in Turkey.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation